Revision of Disphaerobius Attems, 1926 (Chilopoda: Lithobiomorpha: Lithobiidae: Pterygoterginae), a centipede genus with remarkable sexual dimorphism - Farzalieva, Gyulli Sh.; Nefediev, Pavel S.; Tuf, Ivan H. (Zootaxa, 2017)
Disphaerobius Attems, 1926, the sole constituent genus of the subfamily Pterygoterginae, is synonymized with Pterygotergum Verhoeff, 1934 syn. nov., and is shown to comprise only two species: D. svenhedini (Verhoeff, 1934) comb. nov. ex Pterygotergum, and D. loricatus (Sseliwanoff, 1881) (= Lithobius magnificus Trotzina, 1895), both syn. nov. and comb. nov. ex Lithobius Leach, 1814. Disphaerobius is rediagnosed, both of its basically Central Asian species are redescribed from fresh material of both sexes, and their distributions are mapped. Disphaerobius svenhedini is newly recorded from S Kazakhstan and W Mongolia. New material of D. loricatus is also recorded. Sexual dimorphic characters in Lithobiomorpha are briefly discussed, these being considered especially strongly pronounced and unique in Disphaerobius.